Cloning - Dudley, William, 1964- (Opposing viewpoints series (Unnumbered), 2006)
Presents a collection of essays that provide an introduction to cloning, in simple text with illustrations, including an examination of the history, future, and ethical ramifications of cloning, recombinant DNA, and gene therapy.